A Microfluidic Platform with Nanoparticle-Based Metal-Enhanced Fluorescence for pH Mapping Acidified Aqueous Solutions by CO2 Microbubbles. Issue 28 (28th April 2016) - Asselin, Jérémie; Parvinzadeh Gashti, Mazeyar; Boudreau, Denis; Greener, Jesse
ABSTRACT: A method for creating pH maps in microchannels containing liquid/liquid and liquid/gas phases comprised of water and CO2 is demonstrated. It is based on a glass slide coated with nanoparticles exhibiting metal-enhanced fluorescence. The time resolution is better than 500 ms, limited by the fluidic control. This work opens the way for new in situ measurements of physical dissolution and chemical reactions in dynamic CO2 gas-liquid systems.